2013
DOI: 10.1107/s2053230x1303135x
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of DNA recognition by the p202 HINa domain: insights into the inhibition of Aim2-mediated inflammatory signalling

Abstract: PDB reference: p202 HINa domain, 4lnqThe HIN-200 family of proteins play significant roles in inflammation-related processes. Among them, AIM2 (absent in melanoma 2) and IFI16 ( -interferoninducible protein 16) recognize double-stranded DNA to initiate inflammatory responses. In contrast, p202, a mouse interferon-inducible protein containing two HIN domains (HINa and HINb), has been reported to inhibit Aim2-mediated inflammatory signalling in mouse. To understand the inhibitory mechanism, the crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In the absence of DNA ALRs are in an autoinhibited state with PYD and HIN domains. This suggests a mechanism of AIM2 activation in which binding of DNA to the HIN domain releases the PYD from its interaction with the HIN domain, thereby promoting PYD‐PYD interaction with ASC and inflammasome assembly …”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…In the absence of DNA ALRs are in an autoinhibited state with PYD and HIN domains. This suggests a mechanism of AIM2 activation in which binding of DNA to the HIN domain releases the PYD from its interaction with the HIN domain, thereby promoting PYD‐PYD interaction with ASC and inflammasome assembly …”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…Furthermore, studies involving overexpression of AIM2 in transfected cells, followed by immunoprecipitation-Western assays, indicated that the AIM2 protein binds with IFI16 protein [38] and can homodimerize [39]. Interestingly, studies indicated that the HIN domain in certain PYHIN-family proteins also allows proteins to form homo and heterodimers [41][42][43][44][45][46]. For example, the HIN2 domain in the p202 protein formed homodimers and bound to the HIN domain of Aim2 protein [42].…”
Section: Homo and Heterodimerization By Aim2/aim2mentioning
confidence: 99%
“…Expression of p202 is induced by interferon, and as negative feedback regulation p202 inhibits the inflammatory function of AIM2 [14]. Crystal structures of the p202 HIN1/dsDNA complexes show that the two OB folds are very similar to those of AIM2, but that the dsDNA binds p202 HIN1 at an almost opposite surface compared with that used in AIM2 HIN (Figure 3d, 3e) [30, 32, 33]. Surprisingly, the HIN2 domain of p202 does not interact with dsDNA [33].…”
Section: Dna Recognition and Regulation By Alr Hin Domainsmentioning
confidence: 99%
“…First, p202 binds dsDNA at a higher affinity than AIM2, and therefore competes with AIM2 for access to dsDNA. Second, the direct interaction between p202 HIN2 and AIM2 HIN domains may allow incorporation of p202 onto the same dsDNA that AIM2 interacts with, thereby diluting the effective concentration of AIM2 on the dsDNA [30, 32, 33] (Figure 3f). Thus, AIM2 PYD oligomerization and downstream signaling may be inhibited.…”
Section: Dna Recognition and Regulation By Alr Hin Domainsmentioning
confidence: 99%